Comeuppance served cold - Deeds, Marion (Tordotcom, 2022)
In 1929 Seattle, grifter Dolly White applies for a job as a minder to the wealthy Fiona Earnshow, to keep her out of trouble until she can marry the man her father selected. But Dolly is working with powerful magic to protect the shifters in Seattle from a powerful, misogynistic scion.